Evaluasi Program Kepenulisan Berbasis Genre Melalui Pendekatan CIPP (Context, Input, Process, and Product) dalam Mata Kuliah Wajib Umum Bahasa Indonesia - Nurhamidah, Didah; Suseno, Muchlas; Setiadi, Samsi (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to evaluate the genre-based writing program in the Indonesian General Compulsory course at the Faculty of Tarbiyah and Teacher Training (FITK) UIN Syarif Hidayatullah Jakarta by using the CIPP (Context, Input, Process, Product) evaluation model. The research method used is a qualitative approach with a case study design. Data was collected through in-depth interviews, classroom observations, and analysis of program-related documents. The results of the study show that genre-based writing programs are effective in improving students' writing skills, especially in writing essays, scientific articles, and literary works in accordance with the genre taught. The program is relevant to the vision and mission of the university and faculty which aims to produce competent and innovative graduates. However, there are challenges in terms of program policies that do not require students to participate in this program, as well as the need to improve lecturer training in the use of the latest learning technologies. Additionally, although most students feel their writing skills are improving, there is still room for the development of advanced and creative writing skills. This research provides recommendations to strengthen program policies, improve the use of technology, and introduce further challenges in writing tasks to optimize program impact.